2012
DOI: 10.2298/jsc110331161r
|View full text |Cite
|
Sign up to set email alerts
|

The influence of shaped TiO2 nanofillers on thermal properties of polyvinyl alcohol

Abstract: PVA-based nanocomposites consisting of shaped TiO2 nanocrystals (nanoparticles, nanotubes or nanorods) were synthesized by direct blending of polymer and titania nanocrystals solution or powder. In order to elucidate the influence of shape of titania nanocrystals on thermal stability of polymer matrix and particles interaction with PVA chain, structural and thermal characterizations of PVA/TiO2 nanocomposites were performed. Faceted nanoparticles increased the thermal stability of PVA matrix. Titania na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…(5) shows the variation of refractive index (n) with photon energy of the prepared thin films. The increase may be attributed to higher packing density and the changes in the particle size distribution function of TiO2 structural, this the enhancement of growth crystalline this attributed to the molecules of TiO2 come close together when add PVA polymer [3,6] . …”
Section: (3) Refractive Index (N)mentioning
confidence: 99%
See 2 more Smart Citations
“…(5) shows the variation of refractive index (n) with photon energy of the prepared thin films. The increase may be attributed to higher packing density and the changes in the particle size distribution function of TiO2 structural, this the enhancement of growth crystalline this attributed to the molecules of TiO2 come close together when add PVA polymer [3,6] . …”
Section: (3) Refractive Index (N)mentioning
confidence: 99%
“…TiO2 have the outstanding proportion of high refractive index (N2.5), excellent transmittance in visible as well as high electrical and chemical stability. It has been studied extensively for using in optoelectronic device [4,5] TiO2 was used as electron accepting material because of its non-toxic and abundance availability to indentify physical and structural properties of semiconductor material, the scope of thin films has enabled this opportunity to study semiconductors through the preparation of films [6], because of easily breaking the thin film which is does not exceed only microns thick it is deposited on certain substrate ,such as glass, silicon ,and alumina [7] . TiO2 is found naturally as white material, in three forms of crystalline, Rutile (tetragonal), Anatase (tetragonal), and Brokite (orthorhombic) [8] , TiO2 films can be prepared by different techniques, such as thermal evaporation in vacuum deposition (TEVD), chemical vapor deposition (CVD), pulse laser deposition (PLD) chemical spray pyrolysis deposition (CSPD) and other method [9,10,11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2004), Huyen, D. N. et al (2011), Olad, A. et al (2012), Ays, E. et al (2007) and Abduljalil, H. et al (2011), due to their potential applications in chemistry, physics, electronic, optics and biotechnology. Radoicic, M. B. et al (2012) also established that TiO 2 nano particles increased the thermal stability of PANI, whereas Hao, X. and Li, F., (2011) found that it improved the water resistance,due to strong hydrogen bonding interaction with PVA molecules. The yield of PANI was studied by Subramanian, E. et al (2012) and found that it was increased by encapsulation of TiO 2, in PVA.…”
Section: Introductionmentioning
confidence: 98%
“…Life of the composites and their brightness of light emission are enhanced by the existence of semiconductor nanoparticles in polymeric matrices [28]. Nanocomposites impart several advantages such as greater chemical and thermal stability, increased strength, enhanced electrical conductivity, and improved flammability properties to polymeric matrix [29].There are many reports on the synthesis of semiconductor nanoparticles embedded into polymeric matrices [27,28,[30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%